Various methods of cooling sows in outside lots - Ames, D.; Pollmann, S.; Francis, G.; Nichols, David A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Intermittent sprinkling in outside individual sow pens reduces the amount of water used to cool the sow without adversely affecting performance.
Keywords: Swine; Cooling; Sows; Outside lots